Educational Management Strategies For Improving Quality Education In Rural And Urban Primary Schools - Portia Oware Twerefoo; Martin Kudwo Akotey (Universitas Pakuan, 2025)
This study investigates the influence of educational management strategies on the improvement of quality education in rural and urban primary schools. Grounded in Sustainable Development Goal 4 (SDG 4) and systems theory, the research examines how strategic planning, monitoring and supervision, school discipline, and internet facilities contribute to educational quality across different school contexts. A quantitative cross-sectional design was employed involving primary school teachers and school leaders from rural and urban areas. Data were analyzed using Structural Equation Modeling (SEM) to evaluate the direct and mediating relationships among the variables. The findings indicate that effective educational management significantly enhances the quality of education in both rural and urban primary schools. Urban schools demonstrated comparatively higher educational quality due to stronger managerial practices, better infrastructure, and greater access to digital learning resources. Furthermore, internet facilities were found to positively mediate the relationship between educational management and quality education, although limited technological access in rural schools weakened instructional effectiveness and learning outcomes. Monitoring and supervision, strategic planning, and disciplinary management emerged as key determinants of institutional effectiveness and academic improvement. The study highlights the urgent need for equitable educational policies that strengthen managerial capacity, improve digital infrastructure, and expand professional development opportunities for school leaders and teachers, particularly in rural communities. The research contributes to the growing discourse on educational management and school effectiveness in developing countries by providing empirical evidence on contextual disparities between rural and urban primary education systems. The findings also offer practical implications for policymakers, educational administrators, and stakeholders seeking to achieve inclusive and sustainable quality education.